Augmented reality books: in-depth insights into children’s reading engagement - Alhamad, Kawla; Manches, Andrew; McGeown, Sarah (Frontiers in Psychology, 2024)
Children’s reading engagement is associated with the quality of their reading experiences and outcomes; however, research to date has only examined children’s reading engagement within the context of traditional print books or digital texts. Augmented Reality represents a hybrid reading experience, where traditional paper books are augmented with digital features (e.g., animations, sounds, comprehension questions). This is the first study to examine children’s perspectives and experiences of AR books, within the context of reading engagement. In total, 38 demographically diverse children (aged 8–10, 21 male, 17 English as an Additional Language, 14 ethnicities, nine with teacher-reported reading difficulties) from the UK participated. After reading an AR book, children participated in interviews about their reading engagement. Deductive (themes) and inductive (subthemes) approaches to thematic analysis were used, examining children’s AR reading experiences within the context of their behavioral, cognitive, affective and social engagement. The majority of children found AR books easy to use, and provided examples of how AR books supported their behavioral engagement (e.g., desire to read more/extend reading practices), altered their cognitive engagement (e.g., reading strategies, visual representation/use of imagination, comprehension monitoring), influenced their affective engagement: (e.g., diverse positive feelings), and social engagement (e.g., prompted interaction and discussion), providing examples suggesting similarities and differences with traditional print books. This paper provides novel in-depth insights into children’s perspectives and experiences of AR books, and provides a foundation for researchers, educators, and AR book designers interested in better supporting children’s reading experiences and outcomes with AR books.